Unraveling the influence of defects on Sulfonamide adsorption onto Blue-phosphorene nanotube using density functional theory - José M. Vergara; Julian D. Correa; Miguel E. Mora-Ramos; Elizabeth Flórez (PLoS ONE, 2025)
Sulfonamide antibiotics are commonly used in human therapy. Consequently, pharmaceutical residues may seep into the surface and groundwater, contaminating the aquatic environment. Adsorption is the most widely used method for removing these contaminants from water bodies. This study investigates the efficiency of (14, 14) armchair and (14, 0) zigzag blue phosphorene-based nanotubes (BPNT) as adsorbents of three popular toxic antibiotics, Sulfanilamide (SAM), Sulfadimethoxine (SMX), and Sulfadiazine (SDZ), from water bodies. All calculations are performed using density functional theory. Analyzed molecules are weakly adsorbed on the pristine BPNTs with an adsorption energy of about –0.312, –0.285, and –0.377 eV. Further, electronic properties of the antibiotics-adsorbed BPNTs are investigated. The effect of single-vacancy BPNTs on the adsorption affinity of antibiotic molecules was studied. Compared with pristine systems, despite the increase in reactivity of zigzag BPNTs to the sulfonamides, armchair configurations show a transition from bipolar-magnetic semiconductor to a non-magnetic metallic system, suggesting that defective armchair BPNTs can also be employed as a sensor for antibiotic molecules. Single-vacancies increase the Eads values of all studied systems by up to 89%, indicating an improvement in the capacity of BPNTs to adsorb these biologically active sulfonamide-based compounds.